Casting and characterization of tic particulate reinforced az91 magnesium alloy metal matrix composite through stir casting process - Kumar A.; Kumar S.; Mukhopadhyay N.K. (My University, 2025)
A commercial magnesium alloy AZ91 reinforced with different percentage of TiC particulate has been fabricated with stir casting process in this study. The micro structural and mechanical properties of the fabricated composite are also examined. The pin on disk dry sliding wear test is performed with varying the load and sliding speed. The wear mechanism with different loads and sliding speed is discussed. The ultimate tensile strength, yield strength and compression strength is increased with increase in percentage of TiC in AZ91. The wear rate increases with increase in normal load and sling speed. © IAEME Publication.